Inclusive education from teachers' perspective : exploring Chilean teachers' attitudes and self-efficacy - Kuittinen, Elina (2017)
Chile has been moving towards inclusive education. However, there are still many challenges regarding the implementation of inclusion policies. Teachers’ attitudes and self-efficacy are crucial for implementation to be successful. Thus, the purpose of this study was to explore Chilean teachers’ attitudes towards inclusive education and self-efficacy in implementing inclusive practices.